2018
DOI: 10.2478/cerce-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Note: Recording of Some Beetles in Honey Bee Colonies

Abstract: Honey bees are very valuable to human. These social insects contribute in the pollination of many crops. Also, the products from honey bee colonies have many nutritional and medicinal benefits. Thus, keeping honey bees are very valuable and can be considered as source of income to many families. There are many diseases and pests that attack honey bee colonies. The pests attack bee colonies include: hornets, wax moths, bee-eater birds, and beetles. Such challenges can impact the survival and productivity of hon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The small hives beetle (SHB) Aethina tumida Murray (Coleoptera: Nitidulidae) was recorded in some countries including the UK, USA, Italy, Sudan, and Korea (El-Niweiri et al 2008;Palmeri et al 2015 andNeumann et al 2016), but not in Egypt (Hassan andAbou-Shaara et al 2018). SHB invades honey bee colonies and its larvae feed on stored food and wax causing damages to combs.…”
Section: Small Hive Beetlesmentioning
confidence: 99%
“…The small hives beetle (SHB) Aethina tumida Murray (Coleoptera: Nitidulidae) was recorded in some countries including the UK, USA, Italy, Sudan, and Korea (El-Niweiri et al 2008;Palmeri et al 2015 andNeumann et al 2016), but not in Egypt (Hassan andAbou-Shaara et al 2018). SHB invades honey bee colonies and its larvae feed on stored food and wax causing damages to combs.…”
Section: Small Hive Beetlesmentioning
confidence: 99%
“…In fact, LHB has not been detected so far in Europe and some North African countries. A study in Egypt as an example showed the presence of some nitidulid beetles that can attack honeybee colonies without any detection to Large Hive Beetles [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Today, the survival and productivity of honeybee colonies can be affected by several pests, including some beetle species. The major problem for honeybee colonies results from attacks by the Small Hive Beetle Aethina tumida Murray (Family: Nitidulidae), which can invade honeybee colonies to feed on stored pollen [ 29 , 30 , 31 , 32 , 33 , 34 ]. Another common beetle pest for beekeeping is the Large Hive Beetle (LHB).…”
Section: Introductionmentioning
confidence: 99%